2013
DOI: 10.1177/230949901302100132
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Insensitivity to Pain and Anhydrosis: A Report of Two Cases

Abstract: We report on 2 patients with congenital insensitivity to pain and anhydrosis. The first one was a 7-monthold boy who presented with non-traumatic, haematogenous septic dislocation of the right elbow with physeal separation of the distal humerus. The second one was a 3-year-old girl suspected to have Job syndrome with an altered immunological profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Therefore, CIP can manifest with orthopaedic problems such as fractures, joint dislocations, avascular necrosis, heterotopic ossification, osteomyelitis and Charcot's joints [5,6]. Therefore, CIP can manifest with orthopaedic problems such as fractures, joint dislocations, avascular necrosis, heterotopic ossification, osteomyelitis and Charcot's joints [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CIP can manifest with orthopaedic problems such as fractures, joint dislocations, avascular necrosis, heterotopic ossification, osteomyelitis and Charcot's joints [5,6]. Therefore, CIP can manifest with orthopaedic problems such as fractures, joint dislocations, avascular necrosis, heterotopic ossification, osteomyelitis and Charcot's joints [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Minde et al [11] on the basis of a study of a Swedish family with CIP type V, suggested that children usually present between the ages of 4 and 6 years. These patients can also present with chronic or acute on chronic osteomyelitis as the delayed bone healing encourages pathogen colonization and worsening joint destruction [3,5]. A high index of suspicion is essential to establishing an early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Makari et al described two brothers with CIPA who suffered from child abuse [20]. In recent days, two cases of CIPA patients who continue treatment have been reported [21]. Generally, effective CIPA treatment has been established within the framework of family education and patient education [22].…”
Section: Discussionmentioning
confidence: 99%
“…Corneal ulcers are also relatively frequent in patients with CIPA. A differential diagnosis of neurotrophic keratitis may be taken into consideration [ 33 , 34 ]. Among all these diagnostic possibilities and according to Raspall-Chaure [ 29 ],…”
Section: Discussionmentioning
confidence: 99%